The urban flora of Primorsk (Zaporizhia region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
The article contains comprehensive analysis of the current state of biodiversity in urban flora of Primorsk. It has been shown that species composition of urban flora Primorsk (Zaporizhia region) has 556 species of 2 divisions, 61 families and 233 genera. We have analyzed the urban flora of Primorsk in systematic, biomorphological and ecological aspects. Adventive component was analyzed, the main trends of its further development were identified. We shown the main centers of entry alien invasive species of flora, ways and causes their proliferation. It was revealed that Primorsk is characterized by specific urban floras, which combine elements of the natural flora and typical urban components.
Keywords: urban flora, Primorsk, biodiversity, analysis, hydrophilic component, adventive flora.